Studies on meropenem and cefixime metal ion complexes for antibacterial activity - Milind J. Umekar (SpringerOpen, 2021)
Abstract Background The metal ion complexes of meropenem and cefixime with cadmium, silver, palladium, zinc, nickel, cobalt and copper were synthesized and characterized by UV, FTIR and H1-NMR spectrophotometry. The antibacterial effects of the complexes were studied using cup and plate method against S. aureus, B. subtilis, E. coli, P. aeruginosa and K. pneumoniae for normal and resistant strains of bacteria. The minimum inhibitory concentration of the metal ion complexes was determined by broth dilution method. Results UV spectroscopic studies suggested that meropenem ligand form complex with different metal ions and FTIR spectrum confirmed the proposed structure. Similarly, UV spectrum of cefixime metal ion complexes at λ max 202–295 nm and meropenem metal ion complexes at λ max 249–304 nm was observed in all the complexes. FTIR peaks for a proposed structure were observed in all the meropenem and cefixime metal ion, indicating the formation of complexes, and retained the functional groups of drugs. Meropenem as well as cefixime metal ion complexes exhibited more antibacterial activity against all the selected bacterial strains. Specifically, the lowest minimum inhibitory concentration against P. aeruginosa and K. pneumoniae was observed to be 100 and 150 μg/ml, respectively. Conclusion The present study concluded that the meropenem and cefixime metal complexes can exhibit the better treatment than individual drug on normal as well as resistant bacteria.